Alasan dan Langkah Pembangunan Bisnis Berbasis Web - Gautama, Idris (Bina Nusantara University, 2003)
This paper starts with the explanation of e-Commerce, e-Business, types of business, and taxonomy of business models. This paper also explains why starting web-based business from scratch is easier than to transform brick and mortal business to web-based/internet business. Then step-by-step creating web-based business will be explained.